Chemical interactions in Ti doped MgB2 superconducting bulk samples and wires - Haigh, S; Kovac, P; Prikhna, T; Savchuk, Y; Kilburn, MR; Salter, C; Hutchison, J; Grovenor, C (2005)
Magnesium diboride superconducting wires and bulk samples synthesized at high pressure have been produced with a variety of reactive metal additions. All these samples showed high critical current densities, but here we are most interested in the striking result that reactive metal additions such as titanium substantially improved the critical current values, but had little detrimental effect on Tc values. For instance, the critical current values in the wires could be increased by more than a factor of 3.5 at 4 K and 10 T by the inclusion of up to 10 wt% of Ti. In bulk materials the J c values can be increased by even larger values, and the irreversibility field at 20 K increased to above 7 T. In a detailed study of the microstructure of these materials we have shown that PIT ex situ wires with 10 wt% titanium additions have a complicated layered microstructure around the Ti-rich particles, possibly forming titanium-boron phases, but also incorporating impurity elements including hydrogen. X-ray diffraction data, TEM and elemental mapping in the NanoSIMS confirmed the surprising suggestion that samples synthesized at high pressure from Mg and B with Ti additions contain a titanium hydride. These new compositional data support the idea that reactive metal additions are extremely beneficial in MgB2 wires and bulk materials because they preferentially adsorb deleterious impurities from the superconducting matrix. © 2005 IOP Publishing Ltd.